DIFFERENT CHANGES IN THE SMALL INTESTINE IN PULMONARY FIBROSIS. THE BODY'S RESPONSE TO EXPERIMENTAL PULMONARY FIBROSIS (Spectrum Journal of Innovation, Reforms and Development, 2022)
Idiopathic pulmonary fibrosis (IPF) is a devastating disease characterized by severe and progressive scar formation in the gas-exchange regions of the lung. Despite years of research, therapeutic treatments remain elusive and there is a pressing need for deeper mechanistic insights into the pathogenesis of the disease. In this article, we review our current knowledge of the triggers and/or perpetuators of pulmonary fibrosis with special emphasis on the alveolar epithelium and the underlying mesenchyme. In doing so, we raise a number of questions highlighting critical voids and limitations in our current understanding and study of this disease.